Returns To Capital In Microenterprises : Evidence From A Field Experiment - Woodruff, Christopher, 1959- 1959- (The World Bank, 2007)
Small and informal firms account for a large share of employment in developing countries. The rapid expansion of microfinance services is based on the belief that these firms have productive investment opportunities and can enjoy high returns to capital if given the opportunity. However, measuring the return to capital is complicated by unobserved factors such as entrepreneurial ability and demand shocks, which are likely to be correlated with capital stock. The authors use a randomized experiment to overcome this problem and to measure the return to capital for the average microenterprise in their sample, regardless of whether they apply for credit. They accomplish this by providing cash and equipment grants to small firms in Sri Lanka, and measuring the increase in profits arising from this exogenous (positive) shock to capital stock. After controlling for possible spillover effects, the authors find the average real return to capital to be 5.7 percent a month, substantially higher than the market interest rate. They then examine the heterogeneity of treatment effects to explore whether missing credit markets or missing insurance markets are the most likely cause of the high returns. Returns are found to vary with entrepreneurial ability and with measures of other sources of cash within the household, but not to vary with risk aversion or uncertainty